Over View Karakteristik Pengguna Akseptor KB Suntik 3 Bulan di Puskesmas Mlati 1 - Farasati, Niken Dayu; Belian Anugerah Estri (Jurnal Kesehatan Cendikia Jenius, 2024)
Contraception is an effort to prevent pregnancy. Efforts made in contraceptive services can be temporary or permanent. In Indonesia, according to data from the Indonesian Health Profile in 2019, 3-month injectable contraceptive users amounted to 63.7 out of 15,261,014 couples of childbearing age were active contraceptive users, and in 2019, there was no visible increase in the number of injectable contraceptive users; there was 63.7% out of 15,419,826 couples of childbearing age contraceptive users were active.The aim of this research is to provide an overview of the characteristics of 3-month injectable contraceptive acceptors at Puskesmas (Community Health Center) Mlati 1. This research uses a descriptive survey method with a cross-sectional approach. The population of this study were all mothers who used 3-month injectable contraceptives at Puskesmas Mlati 1 for the period of January-October 2023, totaling 58 acceptors. The non-probability sampling technique used was accidental sampling technique. The instrument used was a questionnaire, and the data analysis used frequency distribution. The result of this research showed that most of the respondents had the characteristics of age 20-35 years (75.9%), high school education (67.2%), housewife (75.9%), multiparous parity (51.7%). Most of the respondents had the characteristics of an income of 1.5-2 million (48.3%), most of the respondents had the characteristics of the preventive birth control phase (51.7%), most of the respondents had the characteristics of high knowledge (53.4%). There were 44 respondents (75.9%) aged 20-35 years and 14 respondents (24.1%) aged <20->35 years. High school education was 39 respondents (67.2%), junior high school education was 5 respondents (8.6%) and undergraduate education was 14 respondents (24.1%). The work of mothers who work as IRTs is 44 respondents (75.9%), private as many as 12 respondents (20.7%) and 2 others work as civil servants (3.4%). Parity that most of the respondents were multipara parity as many as 30 respondents (51.7%), Nulipara as many as 25 respondents (43.1%) and the other 3 grandemulti (5.2%). The largest family income is 1.5-2 million, as many as 28 respondents (48.3%), 20 respondents (34.5%) have an income of 2-3 million, and 20 others have an income of >3 million (17.2%). The level of knowledge was obtained with high knowledge about 3-month injectable birth control as many as 31 respondents (53.4%), moderate knowledge as many as 14 respondents (24.1%) and 13 others had low knowledge (22.2%). The suggestion for Puskesmas Mlati 1 is to provide education regarding long-term contraceptive method of family planning so that the family planning acceptors can know the benefits of long-term contraceptive method of family planning.